Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Novel CRTH2 Antagonist BI 1021958 at Single Oral Doses in Healthy Men and Multiple Oral Doses in Men and Women With Well‐Controlled Asthma. (13th June 2017) - Fowler, Andy; Koenen, Rüdiger; Hilbert, James; Blatchford, Jon; Kappeler, Dominik; Benediktus, Ewald; Wood, Chester; Gupta, Abhya
Abstract: BI 1021958, a novel antagonist of the chemoattractant‐receptor‐homologous molecule (CRTH2), targets airway inflammation in asthma by inhibiting prostaglandin binding to CRTH2 receptors. Two phase 1 studies assessed BI 1021958 safety/tolerability and pharmacokinetics (PK)/pharmacodynamics (PD) following single doses in healthy men and multiple doses in men/women with well‐controlled asthma. Studies 1 had 2 parts: a placebo‐controlled, fixed‐sequence, single‐blind, single‐rising‐dose part (n = 56) and a randomized, 2‐way crossover, open‐label, repeated‐dose part studying the food effect on PK/PD (n = 12). Study 2 was a placebo‐controlled, single‐center, double‐blind multiple‐rising‐dose study (n = 84). Primary end points were safety/tolerability and PK/PD (both studies); secondary end points were eosinophil shape change (ESC; study 1) and dose proportionality/linearity following first dose and at steady state (study 2). BI 1021958 was adequately tolerated in both studies; adverse events were infrequent, generally mild to moderate, and occurred similarly in treatment groups. Maximum measured concentration (Cmax ) was achieved in ≤2.5 hours in study 1 and ≤2.0 hours in study 2. BI 1021958 exposure increased proportionally with dose. In study 1, following a single 60‐mg dose, AUC parameters and Cmax were 20% and 15% lower, respectively, after a high‐fat meal compared with the fasted state. After ≥60‐mg single doses (study 1) and >40‐mg multiple doses (study 2), >95% ESC inhibition was observed for ≥24 hours. PK/PD was similar in healthy subjects and subjects with well‐controlled asthma. Data support further investigation of CRTH2 antagonists for the treatment of asthma.